The Uses of Media Education to Reduce the Phenomenon of Cyber Blackmail-A field study of students of Thi Qar University College of mad media and the college of Imam alKadhim media department (Eurasian Journal of Media and Communications, 2025)
The study, titled "The Uses of Media Education in Reducing the Phenomenon of Electronic Blackmail," aims to identify the uses of media education in reducing the phenomenon of electronic blackmail. It also aims to understand the role media education plays in raising awareness of the dangers of electronic blackmail and ways to prevent it. It also aims to understand its impact on individuals' behavior when using social media. It also aims to understand the impact of media education in building critical thinking skills and distinguishing between accurate and misleading information online. The researcher relied on a quantitative survey approach using a questionnaire on a sample of (100) male and female students from the University of Dhi Qar/College of Media and Imam al-Kadhim College (peace be upon him), Department of Media. To answer the main question and subquestions, the researcher reached the following conclusions: Media education contributes to raising digital awareness, which helps individuals understand the potential risks when using the internet and social media. Enhancing critical thinking skills through media education enables individuals to verify the accuracy of information and avoid falling victim to fabricated messages or images that may be used for blackmail. Media and digital literacy promotes a culture of privacy, as individuals learn the importance of protecting their personal data and determining what can be shared online. Media literacy reduces users' overtrust of strangers online, reducing the chances of being drawn into situations that could lead to blackmail. The researcher also recommends the following: Integrating media literacy concepts into school curricula at all educational levels, with a focus on digital safety, privacy, and awareness of cyber risks; organizing workshops and training courses for students, teachers, and parents on how to deal with and prevent cyberbullying; preparing simplified and engaging educational materials that address cyberbullying issues in a way that suits all age groups, with an emphasis on interactive aspects; and launching awareness campaigns through traditional and new media to inform the public about the dangers of cyberbullying and how to prevent it